Epistemological Obstacle of Students in Accomplishing HOTS Test According to Field Dependent Cognitive Style - Widi Candika Pakaya; Fattah Hanurawan (Pascasarjana Universitas Negeri Malang (UM), 2023)
The main goal of this study is to describe the epistemological obstacles faced by students with field-dependent cognitive styles when attempting to solve HOTS questions. This study uses a qualitative-descriptive methodology. The instruments used are cognitive style tests and HOTS questions. Data is collected through interviews and student work. The research subjects were two participants in third-semester PGSD students at Universitas Negeri Gorontalo. In this study, the data were analyzed by identifying the answers of two respondents to the indicators of epistemological barriers that had been done by the students and then interviewing the respondents. The results of this study showed that students with field-dependent cognitive styles encountered epistemological obstacles, such as conceptual, procedural, and operational technical obstacles, for various indicators. DOI: 10.17977/jps.v11i12023p007